Positive predictive value and sensitivity of ICD‐9‐CM codes for identifying pediatric leukemia - Weinmann, Sheila; Francisco, Melanie C.; Kwan, Marilyn L.; Bowles, Erin J. A.; Rahm, Alanna Kulchak; Greenlee, Robert T.; Stout, Natasha K.; Pole, Jason D.; Kushi, Lawrence H.; Smith‐Bindman, Rebecca; Miglioretti, Diana L. (Pediatric blood & cancer, 2022)
Background To facilitate community‐based epidemiologic studies of pediatric leukemia, we validated use of ICD‐9‐CM diagnosis codes to identify pediatric leukemia cases in electronic medical records of six U.S. integrated health plans from 1996–2015 and evaluated the additional contributions of procedure codes for diagnosis/treatment. Procedures Subjects (N = 408) were children and adolescents born in the health systems and enrolled for at least 120 days after the date of the first leukemia ICD‐9‐CM code or tumor registry diagnosis. The gold standard was the health system tumor registry and/or medical record review. We calculated positive predictive value (PPV) and sensitivity by number of ICD‐9‐CM codes received in the 120‐day period following and including the first code. We evaluated whether adding chemotherapy and/or bone marrow biopsy/aspiration procedure codes improved PPV and/or sensitivity. Results Requiring receipt of one or more codes resulted in 99% sensitivity (95% confidence interval [CI]: 98–100%) but poor PPV (70%; 95% CI: 66–75%). Receipt of two or more codes improved PPV to 90% (95% CI: 86–93%) with 96% sensitivity (95% CI: 93–98%). Requiring at least four codes maximized PPV (95%; 95% CI: 92–98%) without sacrificing sensitivity (93%; 95% CI: 89–95%). Across health plans, PPV for four codes ranged from 84–100% and sensitivity ranged from 83–95%. Including at least one code for a bone marrow procedure or chemotherapy treatment had minimal impact on PPV or sensitivity. Conclusions The use of diagnosis codes from the electronic health record has high PPV and sensitivity for identifying leukemia in children and adolescents if more than one code is required.